2015
DOI: 10.1007/s00535-015-1039-2
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection might have a potential role in hepatocyte ballooning in nonalcoholic fatty liver disease

Abstract: The association of H. pylori seropositivity with hepatocyte ballooning suggests that H. pylori infection may represent another contributing factor in the progression from NAFL to NASH. Eradicating H. pylori infection may have therapeutic prospects in NASH treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 52 publications
3
73
1
5
Order By: Relevance
“…This study also found that H. pylori infection could independently predict NASH in logistic regression analysis ( p = 0.003). And it further confirmed that H. pylori infection may represent a contributing factor to NAFLD (Sumida et al, 2015). Similarly, another two studies from Turkey and Japan, respectively, also suggested H. pylori infection as one of the independent risk factors for the development of NAFLD (Takuma, 2011; Sumida et al, 2015).…”
Section: Epidemiology and Clinical Experimentsmentioning
confidence: 57%
See 1 more Smart Citation
“…This study also found that H. pylori infection could independently predict NASH in logistic regression analysis ( p = 0.003). And it further confirmed that H. pylori infection may represent a contributing factor to NAFLD (Sumida et al, 2015). Similarly, another two studies from Turkey and Japan, respectively, also suggested H. pylori infection as one of the independent risk factors for the development of NAFLD (Takuma, 2011; Sumida et al, 2015).…”
Section: Epidemiology and Clinical Experimentsmentioning
confidence: 57%
“…We know that H. pylori infection has been implicated in the pathogenesis of insulin resistance (IR) (Polyzos et al, 2011), which contributes to the development of NAFLD. Recently, many studies have reported that H. pylori infection is closely related to the development of NAFLD (Polyzos et al, 2013a; Sumida et al, 2015). However, the mechanisms underlying NAFLD remains unclear, and therapeutic options to this disorder are fairly limited nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…The contributing effect of HP infection to the development of NAFLD has also been suggested, as well as for the progression from hepatic steatosis to NASH [13, 3638]. In addition to insulin resistance, invasion of HP in the small bowel mucosa might increase intestinal permeability and facilitate the passage of bacterial endotoxins via the portal vein to the liver [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the severity of steatosis in humans has been correlated with the disruption of intercellular tight junctions in the gut, increasing intestinal permeability, and the intestinal bacterial overgrowth in the small bowel microbiota [39]. In a recent work, the prevalence of NASH, the total NAFLD activity score, and the grade of hepatocyte ballooning were significantly higher in patients positive for anti-HP immunoglobulin G than in those negative [36]. Similarly, higher rates of anti-HP IgG were detected in patients with biopsy-proven NAFLD compared to control group [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we describe for the first time the association between high fat dietinduced NAFLD and enhanced Helicobacter genus detection. Even though is a controversial issue [45,46], it has been suggested the role of Helicobacter pilory as a contributing factor in the progression of NAFLD [47][48][49], considering its eradication as effective preventive or treatment measures [50,51]. Interestingly, Helicobacter genus was dramatically reduced by quercetin treatment in our model of NAFLD, corroborating its anti-Helicobacter activity observed in in vitro and in vivo models of infection [52,53], and supporting therapeutic potential of quercetin for prevention of the spectrum of non-alcoholic fatty liver diseases.…”
Section: Thus Quercetin Reduced the Increased Firmicutes/bacteroidetesmentioning
confidence: 99%